A Randomized Trial on the Efficacy of Prophylactic Active Drainage in Prevention of Complications after Pancreaticoduodenectomy. (December 2016) - Jiang, H.; Liu, N.; Zhang, M.; Lu, L.; Dou, R.; Qu, L.
Background and Aims: This randomized controlled trial was conducted to examine whether prophylactic active drainage decreases morbidity associated with pancreati-coduodenectomy. Material and Methods: A prospective, randomized controlled trial was conducted between April 2010 and May 2015 when 160 consecutive patients following elective pancreaticoduodenectomy were randomized intraoperatively to either prophylactic active drainage group or conventional passive drainage group. The main objectives were the incidence of postoperative pancreatic fistula and the associated clinical outcomes. Results: There were 82 patients in the active drain group and 78 patients in the passive drain group. The overall pancreatic fistula rate occurred similarly in the two groups (11.0% (9/82) vs 14.1% (11/78), p = 0.360). Grade C pancreatic fistula in active drain group was significantly less than that in passive drain group (0% (0/82) vs 6.4% (5/78), p = 0.026). The mean postoperative hospital stay and parenteral nutrition support time in active drainage group were shorter than those in passive drainage group (12.6 days vs 14.5 days, p = 0.037; 6.9 days vs 8.6 days, p = 0.047, respectively). Conclusion: Prophylactic active drainage reveals significant reduction in severity of complications associated with pancreatic fistula and might be recommended as an alternative for patients with high risk of developing serious pancreatic fistula after pancreaticoduodenectomy.